ANALISIS TREN CYBERSECURITY PADA INFRASTRUKTUR JARINGAN KOMPUTER MODERN: SYSTEMATIC LITERATURE REVIEW - Ekoputra Wahyu Prakasa; Restu Nugianto; Yustian Servanda (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
Abstract: The development of modern computer network infrastructure has become increasingly complex due to digital transformation, cloud computing, and interconnected devices, leading to significant growth in cybersecurity risks. This condition requires a comprehensive understanding of cybersecurity trends and challenges to strengthen network security systems. This study aims to identify and analyze the main trends and challenges in cybersecurity within modern computer network infrastructure. The research method used is a Systematic Literature Review with a systematic selection process, including identification, screening, and evaluation of relevant scientific articles published between 2021 and 2025. The results indicate that the main trends include the adoption of artificial intelligence for threat detection, the implementation of zero trust architecture, enhanced security in cloud environments, and the rise of automated cyber attacks. Meanwhile, the challenges involve increasing attack complexity, vulnerabilities in network devices, limited human resources in cybersecurity, and the expansion of the attack surface due to modern technology integration. In conclusion, adaptive, proactive, and intelligent technology-based security approaches are essential to address the evolving cybersecurity threats in modern computer network infrastructure.